The Effectiveness of Government Policy on MSMEs Through Empirical Data Analysis in Lampung - Basrowi; Suseno, Bambang Dwi; Yusuf, Furtasan Ali; Utami, Pertiwi (2024)
The purpose of this study is to develop a model of policy synchronization between the central government and local governments and to project strategic goals and objectives to be achieved, as well as future policy directions. The research method used is a quantitative research method with descriptive analysis techniques. The research locus is the Central Government and Banten Province. The research time is May–July 2021. The research stages include primary and secondary data collection, data processing, primary and secondary data analysis, and projection analysis for the years 2021–2025. Based on the results of the analysis, the population policy synchronization model between the central and local governments can be implemented by focusing on government regulations and population control frameworks. This finding is expected to be the basis for stakeholders in synchronizing policies at the regional center so that there are no policy differences between the center and the regions. Central and Regional Government policies must be in line so that it can facilitate the implementation of population control policies in the regions.